Financial literacy and SME resilience in the digital era: A pilot study with extended mediation framework - Marzaidin, Nurul Izzati; Ab Rahman, Siti Maziah; Shaari , Rustam; Ab Rahman, Hasnuddin (Journal of Islamic, Social, Economics and Development, 2025)
This paper offers a pilot study that examines the effect of financial literacy and digital financial literacy on the resilience of Malaysian SMEs in retail and e-commerce sectors, with psychological resilience and dynamic capabilities as mediators. Financial literacy, traditionally defined within knowledge, behavior, and attitudes, has been equated with better decision-making and the survival of a company. But the digital era has placed new demands on SMEs to have not just traditional competences but also digital readiness to enable fintech uptake, e-commerce transactions, and cyber security. Building on Dynamic Capabilities Theory (DCT) and resilience theories, this study constructs an extended mediation model to explain how financial and digital competences are translated into resilience through adaptive organizational capabilities and psychological strengths. Information were collected from a small pilot SME business owner sample for the validation of measurement instruments and testing initial relationships. Findings indicate that financial literacy and digital financial literacy have direct and indirect positive effects on resilience, with dynamic capabilities and psychological resilience mediating the relationship partially. This research intellectually contributes by theoretically applying DCT to the digital finance context and pragmatically by suggesting policy interventions with financial education and psychological resilience training augmented with digital skills for SME owners.